Application of the Multimedia Development Life Cycle (MDLC) Methodology to Build a Multimedia-Based Learning System - Santi Purwanti; Rini Astuti; Jaja Jaja; Rakhmayudhi Rakhmayudhi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Success in the process of teaching and learning activities can be influenced by human resources from both educators and students, besides that success needs to be supported also by the existence of media that can assist the role of educators in delivering teaching materials and helping students to receive teaching materials, so that more interesting and interactive so that it can increase interest in learning. The media used is a multimedia-based learning system using the Multimedia Development Life Cycle (MDLC) methodology, with this methodology can build a system as expected by users in the teaching and learning process, the results of this study are a multimedia-based learning system that contains interactive media there are 6 (six) buttons to lead to the display of lesson plans, materials, exercises and evaluations, additionally added buttons to load the previous and subsequent views so as to make it easier for educators and students.